Clinical features of COVID-19 infection in patients with myasthenia gravis: a real-world retrospective study - Li, Hui-Ning; Xu, Xiao-Na; Qin, Ying-Hui; Liu, Rui; Guo, Wen-Yue; Huang, Xiao-Yu; Fan, Mo-Li; Zhang, Lin-Jie; Qi, Yuan; Zhang, Chao; Yang, Li; Shi, Fu-Dong; et al. (Frontiers in Public Health, 2024)
Objective: We investigated the risk factors associated with severe or critical Coronavirus disease 2019 (COVID-19) infection due to the Omicron variant in patients with myasthenia gravis (MG) and determined the potential effect of COVID-19 on myasthenic exacerbation during the Omicron pandemic. Methods: This retrospective study included 287 patients with MG in Tianjin, China. Clinical data of the patients were collected using electronic questionnaires, databases, and clinical records. Results: The overall infection rate was 84.7%. Advanced age, comorbidities, generalized phenotype and MG instability were drivers of COVID-19 severity, and post-COVID-19 myasthenic exacerbation. The concurrent use of a steroid-sparing agent did not affect COVID-19 susceptibility or severity. It did lower the risk of myasthenic exacerbation after COVID-19 infection. Patients with severe COVID-19 experienced myasthenic exacerbation earlier than patients with non-severe infection (P<0.001). The severity of COVID-19 (Hazards Ratio=3.04, 95% CI: 1.41–6.54, P=0.004) and the clinical phenotype (Hazards Ratio=3.29, 95% CI: 1.63–6.63, P<0.001) emerged as independent risk factors for early MG exacerbation. Conclusions: Generally, patients with MG appear to be susceptible to the Omicron strains. Immunotherapy for MG did not increase COVID-19 susceptibility or severity. We do not advocate an immediate cessation of ongoing immunosuppressive treatments once a COVID-19 infection is diagnosed. Instead, a judicious evaluation of the risks and benefits, tailored to each individual, is recommended.